Menyibak Dimensi Relasionalitas Dalam Tradisi Sako-seng Masyarakat Sikka Sebagai Motivasi Untuk Bergotong-royong (Perspektif Filsafat Relasionalitas Armada Riyanto): Menyibak Dimensi Relasionalitas Dalam Tradisi Sako-seng Masyarakat Sikka Sebagai Motivasi Untuk Bergotong-royong (Perspektif Filsafat Relasionalitas Armada Riyanto) - Sekundus Septo Pigang Ton (Universitas PGRI Adi Buana Surabaya, 2023)
AbstractThe focus of this study is Revealing the Relational Dimensions in the Sako Seng Tradition of the Sikka Community as Motivation for Collaboration (Relational Philosophical Perspective of Armada Riyanto). Sako seng is a farming tradition of the Sikka people which has a relational dimension and motivates the community to live cooperatively. This study aims to reveal the dimension of relationality so that we can know the relationship between humans and nature, humans and each other and humans and God contained in the sako seng tradition. So that this relationship becomes a motivation to work together and help each other in social life. So that from this understanding the tradition of sako seng is preserved. This study used qualitative methods, interviews and observations by collecting data from various sources, books and articles. This research found that sako seng is a tradition that must be preserved because it has elements of the dimensions of the relationship between humans and nature, humans and each other and humans with the Highest Being (God) so that it ultimately leads to a happy life.